Marine electrical technology - Fernandez, Elstan A. (Shroff Publishers and Distributors Pvt.Ltd, 2016)
This book caters to the structured syllabi for Marine Engineering Pre-sea Students, Marine Engineers of all post-sea competency levels and Electro Technical Officers of the Merchant Navy. It can also be used as a reference book in libraries ashore and onboard ships